2012
DOI: 10.1002/ppul.22676
|View full text |Cite
|
Sign up to set email alerts
|

Lung function outcome at school age in very low birth weight children

Abstract: VLBWc at school age showed lung function abnormalities characterized by airway obstruction, hyperinflation, and diffusion impairment. Neonatal lung damage together with preterm birth may play a role in worsening the functional respiratory outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 49 publications
(93 reference statements)
13
84
0
11
Order By: Relevance
“…A reduced lung size and the presence of obstructions may be possible reasons for the increased prevalence of wheezing among these children. These findings are similar to those of the EPICure study (13) and the study by Cazzato et al (14) However, those two studies involved children who were extremely preterm or had very LBW (i.e. < 1,500 g).…”
Section: Discussionsupporting
confidence: 79%
“…A reduced lung size and the presence of obstructions may be possible reasons for the increased prevalence of wheezing among these children. These findings are similar to those of the EPICure study (13) and the study by Cazzato et al (14) However, those two studies involved children who were extremely preterm or had very LBW (i.e. < 1,500 g).…”
Section: Discussionsupporting
confidence: 79%
“…Although some authors have reported a degree of improvement in airway obstruction as BPD subjects grow older [141,142], most longitudinal studies have demonstrated a persistently reduced lung function throughout childhood, adolescence and early adulthood [138,[143][144][145]. Significant functional impairment has also been seen in preterm-born, non-BPD subjects (although less pronounced than in BPD subjects), confirming the important functional impact of prematurity per se even beyond the first year of life [143].…”
Section: Long-term Consequences Of Prematurity and Bpdmentioning
confidence: 73%
“…The proportion of children born at [22][23][24] weeks with lung function below the lower limit of normal was 24% for FVC and 44% for FEV 1 , corresponding to 5-10 times higher risk of a lung function below normal than controls born at term. The proportions for children born at 25-26 weeks of gestation were 11% and 15%, respectively.…”
Section: Gestational Age and Lung Function In Children Born Extremementioning
confidence: 93%